HUBUNGAN JENIS PERSALINAN IBU DENGAN PEMBERIAN KOLOSTRUM DI RSIA MUTIARA HATI GADING REJO PRINGSEWU - Wahyuni, Rini; Rohani, Siti (Bappeda Kabupaten Pringsewu, 2017)
The result of Indonesia's demographic and health survey (SDKI) in 2007-2008 was only 25% of Indonesian infants who received colostrum in the first hour, almost all infants were only 41.4% of colostrum or 58.6% of unborn colostrum (Provincial Health Office Lampung, 2010). Based on the results of 5-day prasurvey at RSIA Mutiara Hati in May 2014, the number of newborns who passed through cesarean delivery as many as 15 babies, infants who were given colostrum as many as 5 infants (33.33%) and infants who do not Given colostrum of 10 infants (66.67%) in May 2014 (Data RSIA Mutiara Hati Gadingrejo, 2014). The type of this research is analytical with Restrospective approach that is with variable result of mother birth type, and variable because that is colostrum value at RSIA Mutiara Hati Gading Rejo Pringsewu Regency year 2014. Measured or at the same time. Samples with accedental sampling. Data in this study used secondary data based on data on all delivery mothers and newborn babies in midwife RSIA Mutiara Hati Gading Rejo.Analisa data used bivariate analysis. From the results of research conducted by mothers suffering from caesarea sectio as much as 70 mothers (55,56%), infants given colostrum counted 41 babies (32,5%), and vaginal delivery as much (44,44%), and not colostrum As much as 19.8%, less than the sectio caesarea and there is a relationship between the type of labor with the benefits of colostrum in RSIA Mutiara Hati Gading Rejo Pringsewu District 2014 (p-value = 0.00), therefore for health can Continue to improve the knowledge of society Especially on the issue of making a pregnancy check on how to maintain health during pregnancy and increase colostrum production.